The Heuristic Power of Agapism in Peirce’s Philosophy (Nóema, 2013)
The first part of this essay provides an analysis of the text “The Law of Mind”, in which Peirce theorizes about the power of growth and spreading of ideas and also presents his response to the classic question about how mind can influence matter. We intended to show, from an analysis focused on the dual semantic meaning of the word “affect”, how the author’s rupture with the Cartesian dualism between mind and matter implies in a substantial identity between ideality and reality by means of a metaphysical merging of realism and idealism, where matter is taken to be only a special case of mind. The second part shows how the forms of evolutionism are drawn from the three categories, highlighting the agapism, the doctrine of cosmic and creative love. Finally, we shall argue on how the association between realism and idealism, as well as the considerations of the author’s evolutionism, constitute vital aspects for the justification of the historical success of our human capacity for conjecturing, viz., for proposing successful hypothesis to explain the facts.
Keywords: Peirce; Mind; Matter; Idealism; Realism; Evolutionism; Agapism; Heuristic